IDENTIFIKASI JENIS-JENIS DAN KANDUNGAN NUTRISI GULMA DI KECAMATAN BATUR, KABUPATEN BANJARNEGARA YANG POTENSIAL SEBAGAI BAHAN PAKAN TERNAK RUMINANSIA - P. Yuwono; T. Warsiti; M. Kasmiatmojo (Udayana University, 2017)
The purpose of this study was to find out the types of weeds and their nutrition content that grow in the planting area of crops in Batur district, Banjarnegara regency potential as ruminant feed. The results showed that at least there were seven types / species of weeds that grows in the Batur village and is often used as an animal feed that were Axonopus compresus (Swarttz) Beauv, Alternanthera sesilis (L) D, C, Lantana camara L., Nasturtium montanum Wall, Commelina benghalensis L ., Cynodon dactylon (L.) Pers, Digitaria adscendens (HBK) Henr. Results of the proximate analysis showed that the weeds have crude protein content ranged from 8.02 to 23.66% and crude fiber content ranged from 19.87 - 39.36%. It could be concluded that the weeds contain crude protein and crude fiber that were pretty good for ruminants. Keywords: weeds, ruminants, crude protein, crude fiber